Learning Interest: How Does the Experimentation of the Technology-Enhanced Learning (TEL) Models? - Ganis Novitriani; Naista Fabella Sari; Merda Arnelita; Kharisma Rizki Aulia; Marina Wati; Nurul Azizah (PT. Pusmedia Group Indonesia, 2025)
This study aims to examine the effectiveness of the Technology Enhanced Learning (TEL) model in increasing students’ learning interest in Islamic Education (PAI) at SMP Negeri 23 Bandar Lampung. The research employed a quantitative method with a quasi-experimental design. The sample consisted of class VIII D as the experimental group and class VIII E as the control group. Data were collected using questionnaires, and the data analysis techniques included normality tests, homogeneity tests, and an independent sample t-test. The findings indicate that the TEL learning model has a positive and significant effect on students’ learning interest, with a significance value of 0.000 (<0.05). Institutionally, this research contributes to the development of learning models that are adaptive to technological advancements and may serve as a reference for schools and teachers in designing technology-integrated curricula. Furthermore, this study enriches the academic literature on the effectiveness of TEL within the specific context of Islamic Education, an area that has received relatively little attention, thereby opening opportunities for further research in technology-based learning innovations.